HABITATS CHARACTERIZATION IN THE TARATIBU, QUIRIMBAS NATIONAL PARK-PNQ, ANCUABE DISTRICT, MOZAMBIQUE (Nativa, 2023)
ABSTRACT: Taratibu was recently declared as a key biodiversity area (KBA) and knowledge on its habitats is very important for the conservation of this area. The present study aimed to identify and describe the main habitats from Taratibu, in PNQ, in order to improve knowledge on its characteristics. For this, techniques of transect, point-square and point-quadrant were used for the vegetation survey and the abiotic parameters of each habitat were determined. Five habitats were described: closed seasonal riparian habitat of Siphonochilus and Rawsonia, with dominance of  Rawsonia lucida, whose IVI was 14%, humid soil, maximum temperatures of 26º C and with 89% canopy cover; semi-closed deciduous forest habitat of Bamboo and Milletia, with dominance of the  Milletia stuhlmannii species, whose IVI was 42%, humid soil, maximum temperatures of 28º C and with 73% canopy cover; open mountain habitat, vellozio-euphorbiaceae-Inselberg, with dominance of the Xerophyta argentea species, whose IVI was 38%, reasonable and dry soil, maximum temperatures of 30ºC and with 0% of tree canopy cover; semi-open Miombo deciduous forest habitat, with dominance of the  Julbernadia globiflora species, whose IVI was 18%, dry soil, maximum temperatures of 28ºC and with 36% canopy cover; and closed Pouteria rain forest habitat, dominated by the Pouteria pseudoracemosa species, whose IVI was 30%, wet soil, maximum temperatures of 28ºC and with 88% canopy cover.Keywords: vegetation; parameters; temperature; soil; luminosity. Caracterização de habitats na concessão de Taratibu, Parque Nacional das Quirimbas-PNQ, Distrito de Ancuabe, Moçambique RESUMO: Taratibu foi declarado recentemente com uma área chave de biodiversidade (KBA) e o conhecimento dos seus habitats é de extrema importância para a sua conservação. O presente estudo teve como objetivo descrever os principais habitats existente em Taratibu-PNQ, com vista a conhecer as suas caraterísticas. Para tal foram utilizadas, técnicas de   transeto, ponto-quadrante e quadrados pontuais para o levantamento da vegetação e foram determinados os parâmetros abióticos de cada habitat. Foram descritos 5 habitats, designadamente: habitat fechado ribeirinho sazonal de Siphonochilus e Rawsonia, com dominância da espécie Rawsonia lucida, cujo IVI foi de 14%, solo húmido, temperaturas máximas de 26º C e com 89% de cobertura de dossel; habitat semi-fechado de floresta caduca de Bambu e Milletia, com dominância da espécie Milletia stuhlmannii, cujo IVI foi de 42%, solo húmido, temperaturas máximas de 28º C e com 73% de cobertura de dossel; habitat aberto de montanha, vellozio-euphorbiaceae- Inselberg, com dominância da espécie Xerophyta argentea, cujo IVI foi de 38%, solo razo e seco, temperaturas máximas de 30ºC e com 0% de cobertura de dossel arboreo; habitat de floresta caduca semi-aberta de Miombo, com dominância da espécie Julbernadia globiflora, cujo IVI foi de 18%, solos seco, temperaturas máximas de 28ºC e com 36% de cobertura de dossel e habitat fechado de floresta Pluvial de Pouteria, dominado pela  espécie Pouteria pseudoracemosa, cujo IVI foi de 30%, solo húmido, temperaturas máximas de 28ºC e com 88% de cobertura de dossel.Palavras-chave: vegetação; parâmetros; temperatura; solo; luminosidade.